CLASSIFYING SOILS AT THE ULTIMATE STAGE OF WEATHERING: A CONTINUING CHALLENGE FOR SUSTAINABLE AGROMANAGEMENT PRACTICES IN THE 21ST CENTURY - Padmanabhan, Eswaran (2010)
Oxisols cover approximately 23% of the land surface in the tropics and are utilized extensively for agricultural purposes in tropical countries. Under the variable input types of agricultural systems practiced locally, some of these soils still appear to have problems in terms of proper soil classification and subsequently, hinder attempts to implement sustainable agro-management protocols. Therefore, the objective of this study is to examine the properties of some Oxisols and closely related soils in order to evaluate the classification of these soils. Soils from several countries in the tropics were used in this study. Field observations, water retention differences, apparent CEC of the subsurface horizons, extractable Fe-oxides and external specific surface areas of the clay fractions showed that many kandic horizons have surface properties that are similar to the oxic horizons. Micromorphology indicated that the genetic transition from the argillic to the oxic involves a diminishing expression of the argillic. It is proposed that the Oxisols be keyed out based only on the presence of an oxic horizon. The proposal provides a better basis for the classification of Malaysian soils and the development of meaningful soil management groups for plantations.